Life cycle environmental sustainability and cumulative energy assessment of biomass pellets biofuel derived from agroforest residues - Rashedi A.; Gul N.; Hussain M.; Hadi R.; Khan N.; Nadeem S.G.; Khanam T.; Asyraf M.R.M.; Kumar V. (Public Library of Science, 2023)
biofuel; carbon dioxide; fossil fuel; lubricating agent; carbon dioxide; starch; water; acidification; agroforestry; Article; ash; biomass; bulk density; Cedrus deodara; combustion; cooking; crop; ecological footprint; ecotoxicity; elemental analysis; energy; environmental factor; environmental impact; environmental sustainability; eutrophication; forest; forestry; greenhouse effect; grinding; heating; life cycle; life cycle assessment; moisture; nonhuman; Sitophilus zeamais; Triticum aestivum; water footprint; water insecurity; animal; biomass; human; life cycle stage; Animals; Biofuels; Biomass; Carbon Dioxide; Crops, Agricultural; Fossil Fuels; Humans; Life Cycle Stages; Starch; Water